A Randomized Controlled Trail on the Efficacy of Topical Olopatadine Hydrochloride 0.1% and Ketotifen Fumarate 0.025% for the Relief of Symptoms of Vernal Keratoconjunctivitis (Medical Forum Monthly, 2020)
Objective: This study was aimed at comparing efficacy of topical Olopatadine Hydrochloride 0.1% and Ketotifen Fumarate 0.025% for the symptomatic relief of VKC related symptoms at Bahawal Victoria Hospital, Bahawalpur.Study Design: Randomized controlled trial study.Place and Duration of Study: This study was conducted at the out-patient department (OPD) of ophthalmology, Bahawal Victoria Hospital, Bahawalpur from October 2019 to March 2020.Materials and Methods: A total of 186 patients of both gender with VKC were enrolled. Through computer generated numbers, patients were randomly divided into 2 equal groups (93 cases in each group). In Group A, topical olopatadine HCL 0.1% was advised 6 hourly whereas patients of Group-B were advised topical ketotifen fumarate 0.025% 6 hourly. All patients were advised a follow up on 7th and 28th day while final outcome was noted on 28th days following the start of treatment. Efficacy among both treatment groups were noted in the form of relief from VKC related symptoms (itching, watering, foreign body sensation, photophobia).Results: Out of a total of 186 patients, there were 111 (59.7%) boys 75 (40.3%) girls. Overall, mean age was 9.47+3.46 years (ranging from 5 to 19 years). Majority of the patients, 104 (55.9%) were below or equal to 10 years of age. At the end of the study period, significantly more number of patients in Group-A had relief in itching, watering and foreign body sensation in comparison to patients in Group B (p<0,05). Overall compliance with treatment in both study groups was excellent and no adverse effects were reported in both study groupsConclusion: Compared to ketotifen fumarate 0.025%, efficacy of olopatadine HCL 0.1% was better in the form of relief of VKC related symptoms. Apparently, no side effects were reported among both study groups while overall compliance with both study drugs was excellent.